The Effectiveness of Acth Therapy According to Etiology in Patients with West Syndrome and Its Long-Term Effects on Bone Mineral Metabolism and Adrenal Pathway - Mesut Güngör; Mine Düzgöl; Hülya Maraş Genç; Emek Uyur Yalçın; Filiz Mine Çizmecioğlu Jones; Bülent Kara (Çocuk Dergisi)
Objective: West syndrome is the most common infantile epileptic encephalopathy, and ACTH or oral corticosteroids are frequently used in its treatment. The aim of this study was to evaluate the efficacy of ACTH therapy and its effects on bone metabolism and adrenal pathway in the subacute-chronic period in a group of children diagnosed with West syndrome. Materials and Methods: Thirty-five children followed up with West syndrome were included in the study for a period ranging from 4 to 68 months after diagnosis. A total of 25 patients were treated with synthetic ACTH. The groups that received and did not receive ACTH treatment were evaluated in terms of seizure control, improvement in EEG findings and neurological prognosis. In addition, the groups that received and did not receive ACTH therapy were compared in terms of bone metabolism changes and adrenal pathway functions. Results: Of the 35 children followed up with the diagnosis of West syndrome, 31 (88.6%) were in the symptomatic group and 4 (11.4%) were in the cryptogenic group. Structural brain anomalies (11 cases) and hypoxic-ischemic encephalopathy (9 cases) were found in the etiology in two-thirds of those in the symptomatic group. ACTH treatment was applied to 22 patients from the symptomatic group and 3 patients from the cryptogenic group. After treatment, complete seizure control was achieved in 15 cases (68.2%) and partial seizure control in 4 cases (18.2%) in the symptomatic group, while complete seizure control was achieved in 2 cases and partial seizure control in 1 case in the cryptogenic group. Although a high rate of improvement in seizure control and EEG findingswith ACTH was detected in the symptomatic group (68.2%), it was observed that the expected improvement in neurological development did not occur. There was no significant difference between bone metabolism and adrenal pathway examinations in cases with and without ACTH, and adrenal insufficiency was not detected in any of the cases. Conclusion: ACTH treatment was effective for West syndrome regardless of the etiology, but severe retardation in neurological development continued despite seizure control in the symptomatic group. It was demonstrated that there is no risk in terms of bone metabolism and adrenal dysfunction in the subacute-chronic period after ACTH treatment.